Transverse and longitudinal Bose-Einstein correlations in antiproton-proton reactions at centre-of-mass energy 630 GeV - October, Faith Joy (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2002.